Assessment of the Sabellaria alveolata reefs’ structural features along the Southern coast of Sicily (Strait of Sicily, Mediterranean Sea) - BORGHESE, JACOPO; ARDUINI, DANIELE; SCHIMMENTI, EUGENIA; IACIOFANO, DAVIDE; MIKAC, BARBARA; BADALAMENTI, FABIO; GIANGRANDE, ADRIANA; GRAVINA, MARIA FLAVIA; MUSCO, LUIGI; LO BRUTTO, SABRINA (Mediterranean Marine Science, 2022)
The honeycomb worm Sabellaria alveolata is a gregarious tube-dwelling polychaete that builds remarkable biogenic reefs in marine coastal waters. Sabellaria alveolata reefs are considered valuable marine habitats requiring protection measures for their conservation, as they play a key role in the functioning of coastal ecosystems. Sabellarid reefs are extensively developed along the Atlantic coasts of Europe and reported for the Mediterranean Sea and the Italian coasts, where large reefs have been recorded in several localities. Fragmentary information is available on their health status, Sabellaria reefs thus being listed as “Data Deficient” in the Red List of Marine Habitats. To fill this knowledge gap, this study focused on the analysis of the structure of three reefs found along the southern coast of Sicily. In particular, we aimed to assess their phases with respect to the natural cycle that characterizes the sabellarid reefs. Reef features were analyzed both on the macroscale, based on the bioconstruction size (diameter and thickness) and degree of fragmentation, and on the microscale, based on the measurement of worm density, opercular length and sand porch presence. This study reveals relevant differences among reefs of the studied locations. These differences we attributeto the temporal shift linked to the natural reef phases, albeit further analyses are needed to understand the possible effect of natural and anthropogenic sources of variation on the Southern Sicilian reefs. In conclusion, Sabellaria reefs are a unique and persistent habitat along the Sicilian coast requiring proper management and conservation measures.